If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(15) = (6x)(4) Multiply 1 * 15 15 = (6x)(4) Remove parenthesis around (6x) 15 = 6x(4) Reorder the terms for easier multiplication: 15 = 6 * 4x Multiply 6 * 4 15 = 24x Solving 15 = 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 15 + -24x = 24x + -24x Combine like terms: 24x + -24x = 0 15 + -24x = 0 Add '-15' to each side of the equation. 15 + -15 + -24x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -24x = 0 + -15 -24x = 0 + -15 Combine like terms: 0 + -15 = -15 -24x = -15 Divide each side by '-24'. x = 0.625 Simplifying x = 0.625
| 18m+8-16=118 | | 5x+3=3(2x+4) | | 19y=29/3 | | 0=-5x-2x | | 18m+8=118 | | 7x^2+8x-15=0 | | 7d+6b=27 | | .66x-.25=.6x+1 | | 1-4(7a-5)=-147 | | 8b-2b-y=4 | | -12t^2+12t+9=0 | | 12t^2-12t-9=0 | | +5=m/5-4 | | -3b+35+2b=95 | | 3/x-5 | | 6p+(2-2p)=6p | | 4(b-8)=7b+4 | | -8.4/2.4 | | 0.04x+0.07*(15000-x)=900 | | (6p+2)-2p=6p | | 84+17=5r+32 | | log(x)+log(x-10)=log(12x) | | 15d+20b=77.5 | | 3=3x-2x+5 | | 7(6+x)=6(2+x) | | 1/5+y=-7/10 | | 4.07-.61x=.82-5.16x | | -(8-5)-1= | | 3/x-5=4/x+5 | | 3b=1/2r-2m | | 3m+2=25 | | 5m+1=26 |